Meat its cookery and digestion - Burtner, Eva Maggy (My University, 1905)
Introduction: As meat is one of the most common as well as the most necessary articles of diet and is used all over our land by rich and poor, its very essential from an economical as well as a hygienic point of view, that we should study the effects of the various methods of preparing meat upon its digestibility. The preparation of meats as well as of other foods has advanced and kept pace with the degree of civilization of man. The savage ate his meat with no preparation whatever but just as it is taken from the animal of his prey. As he became more, advanced in his ideas and tastes he toasted the meat over an open fire. This brought out additional flavors. By the use of these toasted meats a taste for the high flavors was cultivated until now meat is cooked at a very high temperature in order to bring out these high flavors regardless of the fact that it is at the same time rendered more indigestible and less nutritious. For we must remember that as in the case of other foods the value of meat does not depend entirely upon the amount of nutrient present but to some extent upon the amount of these nutrients which the body can digest and use for its support. The term meat as here used includes the several varieties of butcher’s meat as beef, pork, mutton, game and fowl. The value of meat as a food depends upon two distinct classes of nutrients, viz., protein and fat. The protein is essential for the construction and maintenance of the body while both proteids and fats yield muscular power and maintain the temperature.
Citation: Burtner, Eva Maggy. Meat its cookery and digestion. Senior thesis, Kansas State Agricultural College, 1905.
Morse Department of Special Collections
Keywords: Elastin; Albuminoid; Proteid; Theses